Niche divergence between diploid and autotetraploid Tolmiea. Issue 8 (9th August 2016) - Visger, Clayton J.; Germain‐Aubrey, Charlotte C.; Patel, Maya; Sessa, Emily B.; Soltis, Pamela S.; Soltis, Douglas E.
Abstract : PREMISE OF STUDY: Polyploidy is common in eukaryotes and is of major evolutionary importance over both short and long time‐scales. Compared to allopolyploids, autopolyploids remain understudied; they are often morphologically cryptic and frequently remain taxonomically unrecognized, although there is increasing recognition of the high frequency of autopolyploidy in angiosperms. While autopolyploidy can serve as an instant speciation mechanism, little is known about the ecological consequences of this process. We describe the ecological divergence of a diploid‐autotetraploid species pair in Tolmiea . METHODS: We investigated whether abiotic niche divergence has shaped the current allopatric distribution of diploid T. diplomenziesii and its autotetraploid derivative, T. menziesii, in the Pacific Northwest of North America. We employed field measures of light availability, as well as niche modeling and a principal component analysis of environmental space. Within a common garden, we also investigated physiological responses to changes in soil moisture. KEY RESULTS: Diploid and autotetraploid Tolmiea inhabit significantly different climatic niche spaces. The climatic niche divergence between these two species is best explained by a shift in precipitation availability, and we found evidence of differing physiological response to water availability between these species. CONCLUSIONS: We found that spatial segregation of T. diplomenziesii and T. menziesii was accompanied by adaptation to changes in climatic regime. Tolmiea menziesii is not a nascent autotetraploid, having persisted long enough to be established throughout the Pacific Northwest, and therefore both polyploidization and subsequent evolution have contributed to the observed differences between T. menziesii and T. diplomenziesii .